Validation of the Chinese Version of the Body Image Acceptance and Action Questionnaire and the Mediating Role of Body Image Flexibility in the Relationship Between Body Dissatisfaction and Psychological Distress. Issue 3 (May 2021) - He, Jinbo; Cai, Zhihui; Chen, Xinjie; Lu, Tom; Fan, Xitao
Abstract: The psychometric properties of the Chinese version of the Body Image Acceptance and Action Questionnaire (C-BI-AAQ) and its short form (C-BI-AAQ-5) were examined with a sample of Chinese undergraduates ( n = 1, 068, 52.6% female). The factor structure, measurement reliability, measurement invariance across gender, and latent gender mean difference of the two scales were explored. Confirmatory factor analysis was used to examine the factor structure of the C-BI-AAQ and the C-BI-AAQ-5. The original one-factor structure was replicated for both the C-BI-AAQ and the C-BI-AAQ-5. Both the C-BI-AAQ and C-BI-AAQ-5 showed good internal consistency, test-retest reliability, and convergent and discriminant validity (e.g., relationship patterns in the expected directions with theoretically similar psychological flexibility, and with theoretically dissimilar body dissatisfaction, and psychological distress). The C-BI-AAQ-5 was shown to be equivalent to the C-BI-AAQ. Furthermore, strict measurement invariance across gender was confirmed for both the C-BI-AAQ and C-BI-AAQ-5, and latent mean difference tests showed that men had higher levels of body image flexibility than women. Thus, both the C-BI-AAQ and C-BI-AAQ-5 appear to be psychometrically sound instruments for use in the Chinese young adult population. In addition, body image flexibility measured by both the C-BI-AAQ and the C-BI-AAQ-5 fully mediated the relationship between body dissatisfaction and psychological distress. Highlights: BI-AAQ assessing body image flexibility (BIF) was validated in a Chinese sample C-BI-AAQ showed satisfactory reliability, temporal stability, and validity C-BI-AAQ-5 was equivalent to the long form of the C-BI-AAQ C-BI-AAQ and C-BI-AAQ-5 had strict measurement invariance across gender BIF mediated the relation between body dissatisfaction and psychological distress